Identifying Key Steps for Developing Mobile Applications and Mobile Websites for Libraries. - Potnis, Devendra Dilip; Regenstreif Harms, Reynard; Cortez, Edwin (Information Technology & Libraries, 2016)
Mobile applications and mobile websites (MAMW) represent information systems that are increasingly being developed by libraries to better serve their patrons. Because of a lack of in-house IT skills and the knowledge necessary to develop MAMW, a majority of libraries are forced to rely on external IT professionals who may or may not help libraries meet patron needs but instead may deplete libraries' scarce financial resources. This paper applies a system analysis and design perspective to analyze the experience and advice shared by librarians and IT professionals engaged in developing MAMW. This paper identifies key steps and precautions to take while developing MAMW for libraries. It also advises library and information science graduate programs to equip their students with the specific skills and knowledge needed to develop and implement MAMW.